Optimization of anaerobic soil disinfestation against Verticillium wilt in strawberry cultivation using local agrowastes as amendments - Hernández-Muñiz, Paloma; Borrero, Celia; Capote, Nieves; Avilés, Manuel (Frontiers in Plant Science, 2024)
The study explores anaerobic soil disinfection as an alternative to soil fumigants for controlling Verticillium wilt in strawberry crops. For this purpose, two agrowastes close to the strawberry-growing areas of Huelva province were tested as potential amendments for the control of Verticillium wilt: rice bran and residual strawberry extrudate. Furthermore, two application rates were evaluated: 13.50 and 20.00 t/ha for the rice bran and 16.89 and 25.02 t/ha for residual strawberry extrudate. Amended and anaerobically disinfested soils were compared with a non-amended soil under anaerobic conditions, a soil treated with the chemical fungicide metam sodium and an untreated soil. One week before the start of disinfection treatment, these soils were artificially inoculated with 250 microsclerotia/ g dry soil of Verticillium dahliae. After treatments disinfestation, pathogen were quantified, and strawberry plants were cropped in a growth chamber to further evaluate Verticillium wilt severity was measured with a symptom scale in the same potting soils. Measurements of the anaerobic condition, pH and microbial population densities were performed, and the results showed significant differences between the different amendments. In addition, the treatment with rice bran at 20 t/ha recorded the lowest population density of V. dahliae. Likewise, it was possible to achieve a reduction in foliar disease severity in all amended treatments in similar percentage to those obtained by chemical treatment. These results suggest potential application of this technique for the control of Verticillium wilt in the strawberry-growing area of Huelva, reducing the use of chemical fumigants.